Phenotypic Variability in Novel Doublecortin Gene Variants Associated with Subcortical Band Heterotopia - Procopio, Radha; Fortunato, Francesco; Gagliardi, Monica; Talarico, Mariagrazia; Sammarra, Ilaria; Sarubbi, Maria Chiara; Malanga, Donatella; Annesi, Grazia; Gambardella, Antonio (International journal of molecular sciences, 2024)
Doublecortin, encoded by the DCX gene, plays a crucial role in the neuronal migration process during brain development. Pathogenic variants of the DCX gene are the major causes of the “lissencephaly (LIS) spectrum”, which comprehends a milder phenotype like Subcortical Band Heterotopia (SBH) in heterozygous female subjects. We performed targeted sequencing in three unrelated female cases with SBH. We identified three DCX-related variants: a novel missense (c.601A>G: p.Lys201Glu), a novel nonsense (c.210C>G: p.Tyr70*), and a previously identified nonsense (c.907C>T: p.Arg303*) variant. The novel c.601A>G: p.Lys201Glu variant shows a mother–daughter transmission pattern across four generations. The proband exhibits focal epilepsy and achieved seizure freedom with a combination of oxcarbazepine and levetiracetam. All other affected members have no history of epileptic seizures. Brain MRIs of the affected members shows predominant fronto-central SBH with mixed pachygyria on the overlying cortex. The two nonsense variants were identified in two unrelated probands with SBH, severe drug-resistant epilepsy and intellectual disability. These novel DCX variants further expand the genotypic–phenotypic correlations of lissencephaly spectrum disorders. Our documented phenotypic descriptions of three unrelated families provide valuable insights and stimulate further discussions on DCX-SBH cases.